Evidence of validity of the Risk Self-Medication Questionnaire focused on Health Literacy - Márcio Adriano Fernandes Barreto; Francisca Diana da Silva Negreiros; Virna Ribeiro Feitosa Cestari; Helena Alves de Carvalho Sampaio; Thereza Maria Magalhães Moreira (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to analyze the validity evidence of the internal structure of the Risk Self-Medication Questionnaire Focused on Health Literacy. Methods: a psychometric study with 499 adults. The internal structure was assessed with exploratory and confirmatory factor analysis to prove the adjustment. Internal consistency was measured by composite reliability and McDonald's omega coefficient (ω). Results: the parameters revealed a model of 35 items distributed across four factors, explaining 56% of the total variance, with factor loadings ranging from 0.31 to 0.85 and adequate communalities. Accuracy (0.79<ORION<0.98), representativeness (0.89<FDI<0.99), sensitivity (1.92<SR<7.07), factor hope (88.3%< EPTD<97.9%), replicability (0.82<H-Latent<H-observed<0.87) and reliability (ω=0.87) were adequate. The composite reliability ranged from 0.840 to 0.910. Furthermore, good model fit was achieved (TLI = 0.99; CFI = 0.99; GFI = 0.95; RMSEA = 0.02 and RMSR = 0.05). Conclusions: an instrument was obtained with good evidence of structural validity for measuring self-medication.